Distributed Congestion Mitigation and Medium Access in Duty Cycling Wireless Sensor Networks - Hao Liu; Ye Liu (International Journal of Distributed Sensor Networks)
Duty cycling is an efficient design approach to achieve energy efficiency in wireless sensor networks. However, it may aggravate congestion due to long access delay and amplified hidden/exposed terminal problems. This paper first investigates some key facts that impact congestion and deteriorate packet transmission. With above observations, we propose a queue length based contention window adjustment approach, which allows congested nodes having high priority to access the channel. Then, a batch transmission scheme is introduced to drain accumulated packets rapidly. Finally, a random preamble mechanism is designed, so that congested nodes have more chances to get channel when other transmission is happening. Through the experiments on TelosB nodes test-bed using TinyOS, evaluation results show that our proposed schemes can mitigate congestion efficiently and have better performance than traditional approaches.